Pengaruh Model Pembelajaran PJBL (Project Based Learning) Terhadap Kemampuan Berfikir Kreatif Siswa Biologi Sekolah Menengah Atas: A Literature Review - Alda Deria; Muhyiatul Fadilah; Izzatul Kamilatun Nisa; Aprilla Fortuna; Bagas Fajriansyah; Putri Salsabila; Ramos Mardiansyah; Fiana Amara Alika; Lismita Lismita; Upik Junita (Universitas Negeri Padang, 2023)
Education is an effort made by the government to create an atmosphere in the learning process for students to be active in building their potential. In the educational process, students are expected to have religious values, be able to control themselves, personality, intelligent, intellectual, moral, and skilled. Students in schools are asked to have 21st-century skills, namely the appearance known as